Makna mimpi, kematian, dan kecemasan pada cerpen Shirakawa Yo Fune karya Yoshimoto Banana - Jamaan, Fairuz (Japanese Research on Linguistics, Literature, and Culture, 2018)
This article aimed to describe a Â human confusion and inner turmoil that is often found in the lives of modern society in Japan, such as the infidelity, love, death, and anxiety that trigger inner conflict through the analysis of characters in the short story Shirakawa Yo Fune, by Yoshimoto Banana. This article uses Sigmund Freud's theory of literary psychoanalysis. The analysisÂ  shows the lives of characters are so individuayl and does not interact much with the surrounding community, Â so that the death of the only person closest triggers anxiety in the character. Anxiety occurs because the tensions are not well reduced. So each character identifies and displacemen to reduced the anxiety. It also motivates character to carry out defense mechanisms in the form of repression which then dreams, daydreaming and fixation. Furthermore analysis of dreams and daydream shows that these situation in case of Â condensation, displacemen and symbolization.Keywords: fixation, condensation, dream, displacemen, symbolization Â  Penelitian ini meneliti kekalutan dan kekacauan batin manusia yang banyak dijumpai pada kehidupan masyarakat modern di Jepang, seperti perselingkuhan, percintaan, kematian, dan kecemasan yang memicu konflik batin melalui analisis tokoh tokoh pada cerita pendek Shirakawa Yo Fune, karya Yoshimoto Banana. Penelitian mengunakan teori psikoanalisis sastra Sigmund Freud. Analisis yang dilakukan memperlihatkan kehidupan para tokoh yang sangat individual dan tidak banyak berinteraksi dengan masyarakat sekitar sehingga kematian satu-satunya orang terdekat memicu kecemasan pada diri tokoh. Kecemasan terjadi karena ketegangan-keteganganÂ  yang tidak tereduksi dengan baik. Untuk mengatasi ketegangan, masing-masing tokoh melakukan identifikasi dan pemindahan Kecemasan juga memotivasi tokoh untuk melakukan mekanisme pertahanan berupa represi yang kemudiam memicu munculnya mimpi, lamunan serta, fiksasi. Selanjutnya analisis terhadap mimpi dan lamunan menunjukkan bahwa mimpi serta lamunan tersebut telah mengalami kondensasi, pemindahan dan simbolisasiÂ Kata Kunci: Â fiksasi, kondensasi, mimpi, pemindahan, simbolisasi